(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2009)
During the last few years, modern cross-sectional imaging techniques have appeared in Forensic Medicine. Magnetic Resonance Imaging (MRI) and Multislice Computed Tomography (MSCT) are increasingly implemented in Post-mortem examination. These non-invasive techniques can augment and even partially replace traditional autopsy. With the use of these methods, a minimally invasive, objective and investigator-independent documentation of forensic cases can be realised to reach qualitative improvement in forensic pathological investigation.